2021
DOI: 10.1155/2021/9963329
|View full text |Cite
|
Sign up to set email alerts
|

The Exponential Rise of Teledentistry and Patient-Oriented Protective Measures in Southeast Asian Dental Clinics: Concerns, Benefits, and Challenges

Abstract: In the Southeast Asian region, various policies have been advocated by health regulatory bodies that entail protective measures such as face masks, gloves, maintaining distance in public areas, and more. These protective measures are aimed at helping reverse the growth rate of the coronavirus. Dentists in this region have incorporated several changes to their practices to help minimize risks of person-to-person transmission inside dental offices. This narrative review aimed to provide an in-depth overview of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…While a copious amount of information is available on social media platforms a lot may be misleading. Thus, increased responsibility of national or international health care organizations as well as of oneself is important to take care of fraudulent information hence globally effective campaigns should be run to make everyone know about the need for COVID-19 vaccination against this pandemic [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…While a copious amount of information is available on social media platforms a lot may be misleading. Thus, increased responsibility of national or international health care organizations as well as of oneself is important to take care of fraudulent information hence globally effective campaigns should be run to make everyone know about the need for COVID-19 vaccination against this pandemic [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for the year 2021 the interest regarding TD increased, and several articles were published. While Marya et al [35] concentrated their research on the different modalities of using teledentistry, such as storing the data and forwarding them to a dental practitioner, monitoring patients remotely, and live video sessions between dentist and patient, as well as providing virtual oral healthcare via mobile devices, the literature review published by Kumar et al [36] identified the three zones in which TD is used in Malaysia: educational institutions, government-based dental clinics, and private practices.…”
Section: The Use Of Teledentistry During Covid-19mentioning
confidence: 99%
“…Although challenges were encountered with the implementation, including internet speeds, technical issues and political clearance, many clinics in Southeast Asian countries started to apply teledentistry in order to provide diagnosis and follow ups for their patients. 17 A notable difference between high and low-income countries was that developed nations such as the US had already adopted and applied teledentistry prior to the pandemic. The rationale was to increase accessibility to health care services and provide services to rural and remote areas.…”
Section: Dovepressmentioning
confidence: 99%